Efektivitas manajemen risiko dalam meningkatkan ketahanan bisnis UMKM berbasis digital - Maulana, Muhammad Mudzakkir (Maliki Interdisciplinary Journal, 2026)
This study aims to evaluate the effectiveness of risk management in strengthening the resilience of digital-based Micro, Small, and Medium Enterprises (MSMEs). The approach used was desk research, analyzing various journals on risk management, MSME digitalization, and business resilience. The research findings indicate that the use of planned risk management can help MSMEs identify, analyze, and manage various risks, including those related to operations, finance, legal, and technology. In the digital world, risks are increasingly complex due to threats to data security, rapid shifts in market trends, and reliance on digital platforms. Therefore, implementing a risk management framework such as ISO 31000 is crucial for improving MSME preparedness in facing uncertainty Furthermore, this study also shows that combining risk management with digital technology can improve MSMEs' adaptability and competitiveness. Digitalization enables businesses to conduct real-time monitoring, make data-driven decisions, and respond more quickly to market changes. This contributes to increased business resilience, as evidenced by MSMEs' ability to survive crises and maintain business continuity. However, various obstacles remain in its implementation, such as a low understanding of risk management, limited resources, and an unsupportive organizational culture. Therefore, increased understanding, technology utilization, and support from various parties are needed to optimize risk management implementation. This study concludes that efficient risk management integrated with digitalization is a key factor in strengthening the resilience and sustainability of MSME businesses in the digital era.